High-Intensity Interval Versus Moderate-Intensity Continuous Training in Individuals With Parkinson's Disease: Hemodynamic and Functional Adaptation - Fernandes, Bianca [UNESP] (2020)
Purpose: To investigate the effect of high-intensity interval training (HIIT) versus moderate-intensity continuous exercise training (MICE) on hemodynamic and functional variables in individuals with Parkinson's disease. Methods: Twenty participants (13 men) were randomly assigned to a thrice-weekly HIIT (n = 12) or MICE (n = 8) for 12 weeks. Hemodynamic (resting heart rate and blood pressure, carotid femoral pulse wave velocity, endothelial reactivity, and heart rate variability) and functional variables (5-time sit-to-stand, timed up and go, and 6-min walking tests) assessed before and after training. Results: Demographic, hemodynamic and functional variables were similar between groups at baseline. Endothelial reactivity tended to increase after HIIT, but not after MICE, resulting in improved level (similar to 8%, P < .01) of this variable in HIIT versus MICE during follow-up. Six-minute walking test improved after HIIT (10.4 +/- 3.8%, P < .05), but did not change after MICE. Sit to stand improved similarly after HIIT (27.2 +/- 6.1%, P < .05) and MICE (21.5 +/- 5.4%, P < .05). No significant changes were found after HIIT or MICE in any other variable assessed. Conclusion: These results suggest that exercise intensity may influence training-induced adaptation on endothelial reactivity and aerobic capacity in individuals with Parkinson's disease.